Calibration of seasonal transfer equation (Z–R) by data of Doppler weather radar, rainfall gauging station and genetic algorithm method in the Abolabbas watershed (in southwest of Iran) - Adib, Arash; Soori Damirchi Sofla, Masoud; Mirzaei, Seyed Yahya; Mahmoudian Shoushtari, Mohammad; Liaghat, Ali (Water science & technology. Water supply, 2021)
The observed radar reflectivity (Z) converts to rainfall intensity (R) by a transfer function. In the first stage, for calibration of collected data (with time step 15 minutes) by weather radar and determination of the best relation between Z and R, it applied a genetic algorithm (GA) to minimize the amount of root mean square error (RMSE). Although Z = 166R2 (the transfer function in the Khuzestan province of Iran) is an appropriate equation, the GA method distinguished that Z = 110R1.8 (from February to May) and Z = 126R2 (for other months) are the optimum transfer functions for the Abolabbas watershed in Iran. The mean of RMSE of optimum transfer equations is 0.59 mm/hr in the calibration stage and 0.85 mm/hr in the verification stage. In the second stage, the Hydrologic Modeling System (HEC-HMS model) used four types of precipitation data (extracted rainfall data from radar and the optimum transfer equations, Z = 166R2, Z = 200R1.6 and extracted rainfall data from rainfall gauging stations). The calibrated rainfall data by the optimum transfer equations can produce flood hydrographs in which their accuracy is similar to the accuracy of generated flood hydrographs by collected rainfall data of rainfall gauging stations. The mean of RMSE is 0.65 cubic metres per second and the mean or R2 is 0.89 for optimum transfer equations.